Incidence rate of acute reactions in transfusion of blood and its products prepared by Urumia Blood Refinery Center - Salimi, S; Feizi, A; Vanabadi, N (Advances in Nursing & Midwifery, 2010)
Background and aim Blood transfusion is one of essential and important but dangerous parts of today’s medicine in which if appropriate measures have not been done, fatal reactions may occur. Acute hemolytic reactions, febrile reactions, and allergic reactions are among the most important and most prevalent transfusion reactions that happen shortly after its beginning and can lead to considerable mortality and morbidity. The aim of this descriptive study was to investigate the prevalence of acute reactions of blood and its products prepared by Urumia Blood Refinery Center. Materials and methods 3880 blood product units transfused to 1261 patients were studied by convenience sampling method. Various instruments and methods such as sphygmomanometer, thermometer, urine analysis, interview and observation were used for data gathering. Collected data were documented in special forms designed for this purpose. Descriptive statistics were used for data analysis. Findings Among the blood recipients, 604 were female and 657 were male. The most frequent complaints of patients were coldness (22.5%), pruritus (20.1%) and chills (18.1%). The prevalence of acute hemolytic reaction, febrile reaction and allergic reactions were 0.52, 6.2 and 11.1 per 1000 transfusions respectively. Conclusion In spite of improved blood refinement techniques, acute transfusion reactions can lead to significant morbidity and mortality. Therefore, physicians’, nurses’ and midwives’ meticulous attention to early symptoms and signs of acute reactions to transfusion of blood and its products have an important role in preventing adverse outcomes of this life-saving remedy. Keywords: Acute reactions, Blood products, Transfusion, Incidence rate. *Corresponding Author: Salimi, Saleh. Assistant Professor, Nursing Dept., Islamic Azad University, Urumia, Iran. E-mail: salimitr@yahoo.co.uk